Examining the relationship between reproductive empowerment and contraceptive self-injection: Tackling the endogeneity problem - Megan M Lydon; Holly M Burke; Katherine M Anfinson; Tihut Mulugeta; Aderaw Anteneh; Teferi Teklu; Mario Chen (PLoS ONE, 2025)
Background Self-care interventions, including contraceptive self-injectables such as subcutaneous depot medroxyprogesterone acetate (DMPA-SC), are hypothesized to be empowering to users. It is also believed that those who are empowered are more likely to use self-care. Though critical for ensuring equity of these interventions, evidence for the relationship between empowerment and contraceptive self-care is scant. However, studying this relationship is challenging. In addition to the potential reversed causality between these two constructs, empowerment is determined by similar factors as the motivation for using self-care, contributing to an endogeneity problem. If not addressed, endogeneity can lead to incorrect causal assertions. Methods Using data from a study of 400 women in Addis Ababa, Ethiopia who opted to self-inject DMPA-SC, we assessed the directionality between the two constructs. First, we assessed the change in empowerment after participants’ first self-injection. Second, we assessed the effect of empowerment on potential future use of self-injection. To address potential endogeneity, we identified instrumental variables of empowerment and then applied a two-stage regression approach to predict desire to continue self-injecting at follow-up with an instrument for empowerment, controlling for other variables. Results Empowerment scores among the 343 women who were followed-up were high and did not significantly change from baseline to endline. Most women (78%) wanted to continue self-injecting. The following variables were identified and used as instruments: religion, employment status and post-secondary school attendance. The final model did not identify a significant relationship between desire to continue self-injecting and empowerment. The test of exogeneity was marginally significant (p = 0.08). Conclusions We did not find evidence of a significant relationship between reproductive empowerment and desire to continue self-injecting. Though there are limitations to this secondary data analysis, we recommend future research investigate this relationship using the methodology demonstrated to address endogeneity inherent in answering this critical question about self-care interventions.